Factors affecting the death toll of COVID-19 (SARS-CoV-2): evidence from 166 countries - Habtamu Legese; Mekonnen Kumlachew (International Journal of Public Health Science (IJPHS), 2022)
This study investigated the factors that affect the death toll of the COVID-19 on a global scale. A cross-sectional research design has been employed to realize the stated objective. This study employed secondary data (Cross-sectional data) collected for 166 different countries and used both descriptive statistics and regression analysis to analyze the collected data and to address the predefined objective. The ordinary list square (OLS) regression result depicted that temperature has a negative and statistically significant effect on the death toll of COVID-19. On the other hand, the population size and the total number of cases have a positive and statistically significant effect on the death toll of COVID-19. Likewise, the geographical region has a statistically significant effect on the death toll of COVID-19. Based on the findings, this study concludes that temperature variation, regional difference, and population size have a significant effect on the death toll of COCID 19 and shall be considered by governments and policymakers to tackle COVID-19 mortality.